Chemistry In Context - "Hill, Graham"; Holman, John (Nelson, Walton-on-Thames: England, 2000)
This completely revised version matches the latest specifications for Advanced Subsidiary (AS) and Advanced GCE Chemistry. The new full-colour design enhances a modern, relevant course text and the informative diagrams and photographs highlight the importance of chemistry in the 21st century. In each chapter there are in-text and review questions which help the student remain focused and increase their understanding. This coupled with the large bank of examination questions at the end of the book provides students with further opportunity for self-study and revision.
Keywords: Chemistry - Teacher resource